2004
DOI: 10.1111/j.1398-9995.2004.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Rupatadine 10 mg and ebastine 10 mg in seasonal allergic rhinitis: a comparison study

Abstract: Rupatadine 10 mg once daily was clearly superior to placebo in alleviating the symptoms of SAR over a 2-week period. In comparison with ebastine, rupatadine shows a trend towards a better profile as regard several secondary efficacy variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 13 publications
3
43
0
1
Order By: Relevance
“…58 Rupatadine 10mg once daily was compared to ebastine 10 mg once daily and placebo. 59 Significant differences were detected in DTSSm between RU treatment and placebo (33% lower for RU group; p=0.005) after two weeks of treatment. Total symptom scores were 22% lower for RU than for ebastine; however, this could not reach statistical significance.…”
Section: Seasonal Allergic Rhinitismentioning
confidence: 90%
“…58 Rupatadine 10mg once daily was compared to ebastine 10 mg once daily and placebo. 59 Significant differences were detected in DTSSm between RU treatment and placebo (33% lower for RU group; p=0.005) after two weeks of treatment. Total symptom scores were 22% lower for RU than for ebastine; however, this could not reach statistical significance.…”
Section: Seasonal Allergic Rhinitismentioning
confidence: 90%
“…This pathway could be a pharmacological target through the use of PAF-R antagonists, including rupatadine, a novel antihistamine/PAF-R antagonist which has been shown to be effective for allergic rhinitis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Their clinical effect in trials of perennial rhinitis lasting 4 weeks and over is usually small. Oral H 1 -antihistamines improve the patientÕs QOL (1066,1077,1479). One double-blind, placebo-controlled longterm trial found that levocetirizine was cost-effective in the treatment of PER (1066, 1115).…”
Section: 22mentioning
confidence: 99%